Effect of Egg Yolk Powder as An Alternative Extender on The Quality of Bali Bull Spermatozoa - Dina Ardiana; Yusuf, Muhammad; Zulkharnaim, Zulkharnaim (Hasanuddin Journal of Animal Science (HAJAS), 2024)
Semen extender is closely related to the success of artificial insemination to achieve maximum results. Extender aims to increase the volume of semen, provide food substances as a source of energy for spermatozoa provide buffers to maintain pH, osmotic pressure, and electrolyte balance, and prevent the possibility of germ growth. This study aims to determine the effect of extender on the quality of Bali bull spermatozoa through an alternative approach, one of which uses Tris-Egg Yolk powder extender, which is efficient and effective. The study was designed randomized, with three treatments and five replications. The treatment combinations were P0 (Tris-Fresh Egg Yolk 20%), P1 (Tris Oven Egg Yolk 20%), and P2 (Tris-Commercial Egg Yolk 20%). The results of analysis of variance showed that in the parameters of progressive motility, viability, abnormality and intact plasma membrane, treatment of P0 (Tris-Fresh Egg Yolk 20%) tended to be similar as treatment P1 (Tris-Oven Egg Yolk 20%) (P>0.05), but in P2 (Tris-Commercial Egg Yolk 20%) was significantly lower (P<0.05) than P0 and P1. It can be concluded that oven egg yolk powder mixed with tris solution can maintain sperm quality after dilution. Keywords: Oven egg yolk powder, commercial egg yolk powder, buffer solution